Male zooid extracts of Antheraea pernyi ameliorates non-alcoholic fatty liver disease and intestinal dysbacteriosis in mice induced by a high-fat diet - Zhu, Lin; Wang, Na; Guo, Guang; Fan, ZuoQing; Shi, XinQin; Ji, XianLing (Frontiers in Cellular and Infection Microbiology, 2022)
The male zooid of Antheraea pernyi (A. pernyi) accumulates several nutrients and physiological activity-related substances for reproduction. Some components in the extracts of the male zooid of A. pernyi (EMZAP) have several functions, such as protecting the liver, enhancing immunity, antiatheroscloresis, anti-aging, and antitumor effects. In this study, we investigated the ameliorating effects on high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD). The EMZAP treatment could ameliorate NAFLD and effectively decrease the serum total cholesterol, triglyceride and low-density lipoprotein levels and a significant increase in serum high-density lipoprotein levels was observed. Additionally, the EMZAP treatment reduced the levels of liver-function enzymes and pro-inflammatory cytokines (i.e., IL-6, IL-8, TNF-α, TGF-β1) and also the oxidative stress indices and regulated the expression of genes associated with fatty acid metabolism (SREBP-1c, PPARα, ACOX-1, CPT-1) in the liver to prevent the development of NAFLD. Furthermore, EMZAP enhanced the diversity and richness of the beneficial intestinal microbes, suggesting its potential as a dietary supplement and functional food to combat NAFLD induced by HFD.